The carbon footprint of an Icelander: A consumption based assessment using the Eora MRIO database - Clarke, Jack Challis, 1988- (2017)
The thesis details the first ever consumption based carbon footprint analysis of Iceland, focussing on both the national carbon footprint and the carbon footprint of Icelandic households. Decarbonisation of stationary energy supply systems, particularly electricity grids, is the current focus of climate change mitigation policy for many nations (UNFCCC, 2015b). However, considerable emissions occur in addition to the supply of electricity and heat, for example, from combustion of transport fuels and emissions embodied in imported goods. The consumption-based carbon footprint (CBCF) is increasingly used to analyse the full scope of greenhouse gas (GHG) emissions for which a nation is responsible (Larsen & Hertwich, 2009; Wiedmann, 2009). This thesis presents the first CBCF analysis of Iceland, a nation with an almost fully decarbonised electricity and heat supply. As well as informing national climate change policy, this study of Iceland may be viewed as a demonstration case for other rich nations of the world, who will face a similar emissions challenge once their own stationary energy supply has been decarbonised. This study combines the 2010-12 Icelandic Household Expenditure Survey with the Multi-Regional Input-Output (MRIO) database Eora to calculate the CBCF of Iceland, with a specific focus on Icelandic households. The annual Icelandic CBCF was 7,164 ktCO2eq (22.5 tCO2eq/capita) on average over the period 2010-12, approximately 55% higher than the production-based carbon footprint, indicating that imported goods consumed in Iceland create significant GHG emissions abroad. The CBCF of Icelandic households is 3,322 ktCO2eq (10.4 tCO2eq/capita, 22.5 tCO2eq/household) over the same period, comprising 46% of the national CBCF. In comparison with recent MRIO results (Ivanova et al., 2016) Icelandic households have a similar CBCF to Norwegian households, despite an almost entirely decarbonised stationary energy supply. Approximately 61% of household emissions were attributed to consumption categories ...